PENGARUH TERPAAN SALES PROMOTION SHOPEE DAN INTENSITAS KOMUNIKASI PEER GROUP TERHADAP PERILAKU IMPULSE BUYING PRODUK FASHION DI PLATFORM SHOPEE PADA GEN Z DI KOTA SEMARANG - Febriandani, Anisa; Setyabudi, Djoko; Pradekso, Tandiyo (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
The surge in purchasing Gen Z fashion products is evidenced by Gen Z holding the highest rank in fashion transactions on e-commerce platforms. These purchases often lead to impulse buying behavior. From a consumer perspective, impulse buying is viewed negatively, yet it positively impacts sellers. Accordingly, fashion stores strive to enhance impulse buying through marketing strategies, including increased exposure to sales promotions and intensified peer group communication. By using this strategy, ideally it can be effective in encouraging impulse buying behavior, but in reality the widespread exposure to sales promotions and peer group communication has not consistently driven impulse buying. This study aims to investigate the influence of Shopee's sales promotion exposure and peer group communication intensity on impulse buying behavior of fashion products among Gen Z on the Shopee platform in Semarang. The research builds on previous studies, using simple linear regression analysis with non-probability convenience sampling of 100 participants aged 18-26 years in Semarang. The hypothesis results show that there is no effect of exposure sales promotion Shopee towards impulse buying behavior fashion product Shopee for Gen Z in the city of Semarang with a sig value. amounting to 0.399. Meanwhile, regarding the intensity of communication peer group there is influence with behavior impulse buying product fashion Shopee for Gen Z in the city of Semarang with a sig value of 0.019.